Measuring Internal Customer Satisfaction Using Net Promoter Score: Case Study on Digital Product - Yusmansyah , Erfizal Fikri; Martinis, Syafrizal; Sulyani , Agnesia Candra; Nurhasanah, Hasna; Rivianto, R. Danisworo Wicaksono (International Journal of Membrane Science and Technology, 2023)
Digitally oriented companies with the primary business process of making digital products are greatly influenced by customer satisfaction. Customer satisfaction can be used as an indicator of the success of a product or service. If customer expectations are met, the satisfaction level will also be high. However, if their expectations are not met, this can have a fatal impact on the company. There are usually two different types of customers: internal and external. This study aims to measure inner customer satisfaction to ensure that the digital products being marketed have received support internally before hoping to get an excellent external response. As for digital product objects in this study, they are divided into several categories, namely wholesale, agriculture, fishery, and poultry, education, healthcare, productivity, utilities, e-commerce, and finance.